2018
DOI: 10.1038/nature25764
|View full text |Cite
|
Sign up to set email alerts
|

Redox-influenced seismic properties of upper-mantle olivine

Abstract: Lateral variations of seismic wave speeds and attenuation (dissipation of strain energy) in the Earth's upper mantle have the potential to map key characteristics such as temperature, major-element composition, melt fraction and water content. The inversion of these data into meaningful representations of physical properties requires a robust understanding of the micromechanical processes that affect the propagation of seismic waves. Structurally bound water (hydroxyl) is believed to affect seismic properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
118
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(119 citation statements)
references
References 37 publications
0
118
1
Order By: Relevance
“…These vacancies can influence the mechanical properties of olivine, for instance by enhancing seismic attenuation due to grain boundary mechanisms (Cline et al 2018). The solubility of common trivalent elements in olivine is sufficiently high that vacancies created by the substitution reaction (5) can greatly outnumber intrinsic vacancies, such as those associated with Schottky defects (van Orman et al 2009 (Stocker 1978).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These vacancies can influence the mechanical properties of olivine, for instance by enhancing seismic attenuation due to grain boundary mechanisms (Cline et al 2018). The solubility of common trivalent elements in olivine is sufficiently high that vacancies created by the substitution reaction (5) can greatly outnumber intrinsic vacancies, such as those associated with Schottky defects (van Orman et al 2009 (Stocker 1978).…”
Section: Discussionmentioning
confidence: 99%
“…The two mechanisms for creating mobile M-site vacancies may co-exist, particularly in mantle wedges above subduction zones, which are oxidized by fluid transfer from the subducting slab (Kelley and Cottrell 2009). High oxygen fugacity has been shown to enhance seismic attenuation in olivine (Cline et al 2018). The similarly high oxygen fugacities present in the earlier deformation experiments of Faul et al (2016), produced by the platinum sleeve used to wrap the specimen (Faul et al 2017 In this study we use computational simulations to investigate the possibility that cation vacancies may be able to lubricate dislocation glide in forsterite by reducing the Peierls stress  p ., providing a mechanism by which point defects may influence the rheology of this important mantle mineral in the glide-controlled creep regime.…”
Section: Introductionmentioning
confidence: 99%
“…But it was not always so. In the 1960s, biologist Joseph Altman reported that new neurons are generated in the adult brain, specifically in a hippocampal subregion called the dentate gyrus, which is now known to be crucial for memory 2 . Further research languished, however, owing to scepticism about the brain's capacity for such dramatic plasticity.…”
Section: Tetsuo Irifune Andmentioning
confidence: 99%
“…Contrary to general thinking, this attenuation seems to be strongly affected by oxidation conditions, rather than by water content. See Letter p.355 2 subjected aggregates of olivine to high temperatures and pressures, and to oscillations that mimic seismic waves known as shear waves. They discovered that the speed and attenuation of the waves were insensitive to the water content of olivine, but strongly dependent on oxidation conditions -findings that could reshape our view of the upper mantle.…”
Section: Oxidation Softens Mantle Rocksmentioning
confidence: 99%
See 1 more Smart Citation